Information Quality, Service Quality, System Quality, User Satisfaction, System Use, dan Net Benefits - Luh Nidiacitra; Gede Sri Darma (Universitas Pendidikan Nasional, 2022)
Banking developments that adopt digital technology are growing rapidly. This is not spared from the competition between financial institutions which is very tight. One of them is the banking sector. This study aims to analyze the factors that influence Bank BNI customers in using digital service machines, namely Digi CS using the Digital Customer Service Machine Using the Human Organization Technology (HOT-FIT) Model. Location this research was conducted at Bank BNI Renon Branch, Denpasar City, Bali Province. This research is a descriptive quantitative research with 134 respondents who are customers of Bank BNI Renon Branch as a sample using accidental sampling. Data were obtained through open questionnaires with an interval scale of 1 to 10 points which were distributed to measure or obtain opinions or responses from customers regarding the eight variables in this study, namely System Quality, Information Quality, Service Quality, System Use, User Satisfaction, Organization Structure, Environment and Net Benefits. Data analysis in this study used Structural Equation Modeling (SEM) through the Part Lease Square (PLS) approach with the SmartPLS 3.2 program. The results of the study show that the Technology Factor, namely the Information Quality, Service Quality, System Quality variables, has an influence on the human factor, namely System Use, User Satisfaction where the human factor also influences Net Benefits. In addition, organizational factors, namely Structure, have an effect on net benefits, but not on Environment, which do not affect net benefits.